信. 不信. Oh... really? : a personal exploration of chinese superstitions in our modern society - Tan, Guan Han (2017)
Having lived with ethnic folk superstitions and taboos, its holding powers of imaginations and influence has deeply intrigued the artist from young. Superstitions however, are losing hold of their influence with contemporary societies, while some interesting customs are being blindly followed. This project seeks out the relevance and underlying meanings to superstitions and taboos which still holds true to the Millennial Generation (years 1980-2000), and also aims to surface notable values that can be found in Chinese superstitions, through Visual Communication Design.